El Riesgo País de Ecuador y su influencia en la captación de Inversión Extranjera Directa - Rodríguez Manzanillas, Anddy Daniel (2025)
Country risk is an indicator that reflects investors' perception of a nation’s ability to fulfill its financial commitments, directly influencing foreign investment attraction and confidence in the international market. The objective of the present research was to analyze Ecuador's country risk and its influence on Inversión Extranjera Directa (IED), given its significance in the nation’s economic and social development. A mixed-methods approach was employed, with a descriptive scope followed by an explanatory phase, utilizing monthly data from 2018 to 2023 and multiple regression econometric models. The analysis examined economic, political, and social factors affecting country risk and its relationship with IED, incorporating control variables such as exports and inflation. The results were statistically significant, demonstrating that an increase in the Indicador del Riesgo País (IRP) leads to a decline in IED flows in Ecuador. This effect is primarily driven by perceptions of instability and higher financing costs, negatively impacting economic growth and financial stability. The findings underscore the importance of public policies aimed at reducing the country’s risk through improvements in governance, political stability, and the creation of a more attractive environment for IED.